Translocation of Foliar Absorbed Zn in Sunflower (Helianthus annuus) Leaves - Li, Cui; Wang, Linlin; Wu, Jingtao; Blamey, F. Pax C.; Wang, Nina; Chen, Yanlong; Ye, Yin; Wang, Lei; Paterson, David J.; Read, Thea L.; Wang, Peng; Lombi, Enzo; et al. (Frontiers in Plant Science, 2022)
Foliar Zn fertilization is an important approach for overcoming crop Zn deficiency, yet little is known regarding the subsequent translocation of this foliar-applied Zn. Using synchrotron-based X-ray florescence microscopy (XFM) and transcriptome analysis, the present study examined the translocation of foliar absorbed Zn in sunflower (Helianthus annuus) leaves. Although bulk analyses showed that there had been minimal translocation of the absorbed Zn out of the leaf within 7 d, in situ analyses showed that the distribution of Zn in the leaf had changed with time. Specifically, when Zn was applied to the leaf for 0.5 h and then removed, the Zn primarily accumulated within the upper and lower epidermal layers (when examined after 3 h), but when examined after 24 h, the Zn had moved to the vascular tissues. Transcriptome analyses identified out a range of genes involved in stress response, cell wall reinforcement, and binding that were initially up-regulated following foliar Zn application, whereas they were down-regulated after 24 h. These observations suggest that foliar Zn application caused a rapid stress to the leaf, with the initial Zn accumulation in epidermis as a detoxification strategy, but that once this stress decreased the Zn was then moved to the vascular tissues. Overall, this study has shown that despite foliar Zn application causing a rapid stress to the leaf and that most of the Zn stayed within the leaf over 7 d, the distribution of Zn in the leaf had changed, with Zn mostly located in the vascular tissues 24 h after the Zn had been applied. Not only do the data presented herein provide new insight for improving the efficiency of foliar Zn fertilizers, but our approach of combining XFM with transcriptome methodological system provides a novel approach for the study of element translocation in plants.